Analysis of Durian Business at UD. Rama Durian, Bebetin Village, Sawan District, Buleleng Regency - Arnawa, Gede; Suardana, Gede; Arta Jiwa, Dewa Nyoman (Widya Amerta, 2025)
Durian, known as the “king of fruits,” plays a vital role in both local andinternational markets, offering promising economic opportunities. This studyanalyzes the business activities of UD. Rama Durian in Bebetin Village, SawanDistrict, Buleleng Regency, Bali, which has operated for more than seven years asa local durian supplier. The objectives are to examine the production andmarketing processes, identify key success factors, and formulate developmentstrategies to enhance income and profitability. Using a descriptive quantitativeapproach, data were collected through observation, interviews, documentation,and questionnaires, and analyzed with descriptive methods and SWOT analysis.The findings show that internal factors such as product quality, inventorymanagement, marketing networks, and financial management significantlyinfluence business performance, while external factors include seasonal climate,supply consistency, competition, consumer demand trends, and governmentpolicies. The results suggest that improving production quality, strengtheningmarketing strategies, building partnerships with local farmers, and diversifyingdurian products are essential for sustainable growth. This research contributes toagribusiness management knowledge and provides practical recommendations forfarmers, entrepreneurs, and policymakers to support the development of thedurian sector and local economic growth in Buleleng.